2017
DOI: 10.1111/jfpp.13361
|View full text |Cite
|
Sign up to set email alerts
|

Rheological and nutritional studies of amaranth enriched wheatchapatti(Indian flat bread)

Abstract: Chapatti made from whole wheat is a popular staple food in India. This article reports incorporation of amaranth (Amaranthus hypochondriacus) flour (20-50%) in wheat flour to get improved rolling properties and better nutrition in terms of proteins and micronutrients. Rheological studies of whole wheat flour (control) and amaranth-wheat combinations using farinograph revealed that amaranth flour (AF) addition up to 50% led to a decrease in percentage water absorption (84.80-77.55%) and dough stability (1.6-0.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
20
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 33 publications
5
20
0
7
Order By: Relevance
“…More recently, the investigations with A. hypochondriacus as a bakery ingredient were substituted up to 25 % level (Kamoto et al, 2018) or in specific breads without fermentation (Banerji et al, 2018). However, there is a lack of information about the effect of replacing wheat flour with other amaranth species, such as A. spinosus.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the investigations with A. hypochondriacus as a bakery ingredient were substituted up to 25 % level (Kamoto et al, 2018) or in specific breads without fermentation (Banerji et al, 2018). However, there is a lack of information about the effect of replacing wheat flour with other amaranth species, such as A. spinosus.…”
Section: Introductionmentioning
confidence: 99%
“…The work [9] presents the results of studies regarding the addition of 20 to 50 % amaranth flour to wheat flour in the chapati technology (traditional bread in India). It was found that the content of amaranth flour improves the properties of the dough, reduces water absorption and stability of the dough, and also increases the total content of protein and trace elements in the final product.…”
Section: Methods Of Determining the Amino Acid Composition Of The Pmentioning
confidence: 99%
“…The studies presented in [6][7][8][9][10][11][12][13] have been carried out using a mixture of wheat flour and flour of various oilseeds or their meal only with the aim of expanding the range of flour products and using secondary processing products, but not to obtain products with increased biological and nutritional value. Therefore, research on the development of food system formulations based on wheat flour, which will have a balanced amino acid composition, is promising.…”
Section: Methods Of Determining the Amino Acid Composition Of The Pmentioning
confidence: 99%
See 2 more Smart Citations